Development of a Value-Clarification-Technique Learning Model Oriented toward Digital Technology Literacy to Foster National Values - Kadir, Abdul; Arisa, Arisa; Hanafi , Muhammad; Sadapotto , Andi; Muthmainnah, Muthmainnah; Kadir, M. Fachmy Achdan; Cardoso, Luis; Korten, Christopher; AlSaghbini, Hisham (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
This research aimed to: 1) innovate learning models using the Value Clarification Technique (VCT) oriented toward improving students’ digital literacy to foster national values at State Junior High School/SMPN 4 Sengkang, and 2) identify the problems in implementing this innovative learning model to promote digital literacy and national values at State Junior High School/SMPN 4 Sengkang. This study was a research and development study that used the Design-Based Research (DBR) approach. The approach included problem identification and analysis, solution design, iterative cycles of testing and refinement, and reflection to produce design principles and implementation guidelines. Data was collected through observation, interviews, documentation, and questionnaires. The data analysis used an interactive model, including data collection, reduction, presentation, and conclusion. The research showed that the innovative learning model based on the Value Clarification Technique successfully improved students’ digital literacy and fostered national values. However, obstacles in implementing this innovative learning model, including inadequate student facilities for online learning at home, affected students’ participation in online learning. In addition, the teachers, especially in group one, tended to focus only on sharing materials and assignments during online learning, which could make students feel bored.